Synthesis and structural characterization of a new polymeric zinc(II) complex with thiophene-2-carboxylic acid - Cagnin, F. [UNESP]; Castellano, E. E.; Davolos, Marian Rosaly [UNESP] (Taylor & Francis Ltd, 2010)
A new polymeric zinc(II) complex with thiophene-2-carboxylic acid (-tpc) of composition [Zn2(C20H12O8S4)]n was obtained and structurally characterized by X-ray diffraction, thermal analysis, nuclear magnetic resonance (NMR), and infrared spectroscopies. Upfield shift in the 1H-NMR spectrum is explained by the crystalline structure, which shows the thiophene rings overlapping each other in parallel pairs. The compound crystallizes in the monoclinic system, space group P21/c, with a = 9.7074(4) angstrom, b = 13.5227(3) angstrom, c = 18.9735(7) angstrom, = 95.797(10)degrees, and Z = 4. Three -tpc groups bridge between two Zn(II) ions through oxygens and the fourth one bridges between one of these ions and the third one, symmetry related by a twofold screw axis. This arrangement gives rise to infinite chains along the crystallographic a direction. The metal atoms display an approximate tetrahedral configuration. The complex is insoluble in water, ethanol, and acetone, but soluble in dimethyl sulfoxide.
Keywords: Polymeric zinc complex; Thiophene-2-carboxylic acid; Crystal structure; 1H-and 13C-NMR